Recovery of indium from LCD screens - Virolainen, Sami; Paatero, Erkki; Ibana, Don (Gecamin Ltda, 2011)
The amount of LCD screens used as computer displays and TVs, has been rapidly growing during the last decade. Since the lifetime of an LCD screen is only a few years, the amount of waste LCDs is growing. Indium exists in LCDs as indium tin oxide (ITO) and according to the literature the amount of indium per 15” display is about 500 mg. Therefore recovering indium from such a secondary raw material becomes economically and environmentally interesting. In the present work, the recovery of indium from crushed LCD screens was studied by acid leaching followed by solvent extraction. Selectivity experiments for solvent extraction were done with solutions obtained from synthetic ITO powder and loading experiments as well as theoretical McCabe-Thiele analysis for authentic LCD powder solution. Leaching experiments were made with1 M H2SO4 with L/S ratios of 3:1 and 10:1. The dissolution of metals is slow; only 37% of the indium available to acid was leached within six hours and 44% in a day. The amount available to acid (tested with 10 M HCl) was significantly lower than expected. In selectivity experiments two different extractants and one extractant blend were used: D2EHPA, TBP and an 1:4 mixture of these. With TBP and mixture reagent, tin could be selectively extracted from ~1.5 M HCl. D2EHPAis a very strong extractant for indium especially from H2SO4 media, but selectivity over tin cannot be achieved. Though, selectivity can be achieved from over 3 M HCl solutions or by stripping from loaded D2EHPA with over 1.5 M HCl. A more detailed theoretical study was made to the option using 1 M H2SO4 for dissolution, 20 wt.% D2EHPA for extraction and 1.5 M HCl for stripping. Based on the McCabe-Thiele analysis, HCl solution containing 6.5 g/L of indium can be obtained with two extraction and stripping stages.